Measurement of Bank Performance in Nepal - Silwal, Abin (Nepalese Journal of Finance, 2024)
This study examines the measurements of performance in the context of Nepalese commercial banks. Return on assets and return on equity are the selected dependent variables. The selected independent variables are capital adequacy ratio, leverage, liquidity, non-performing loan, bank size, GDP growth and inflation. The study is based on secondary data of 15 commercial banks with 135 observations for the study period from 2014/15 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, reports published by Ministry of Finance and annual report of respective commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of capital adequacy ratio, leverage, liquidity, non-performing loan, bank size, GDP growth and inflation on the profitability of Nepalese commercial banks. The study showed that liquidity has a negative impact on return on assets and return on equity. It means that increase in liquidity ratio leads to decrease in return on assets and return on equity. Likewise, leverage has a negative impact on return on assets and return on equity. It shows that higher the leverage ratio, lower would be the return on assets and return on equity. Moreover, non-performing loan has a negative impact on return on assets and return on equity. It means that increase in non-performing loan leads to decrease in return on assets and return on equity. In addition, inflation has a negative impact on return on assets. It indicates that increase in inflation leads to decrease in return on assets. Similarly, GDP growth has a positive impact on return on assets and return on equity. It means that higher the GDP growth rate, higher would be the return on assets and return on equity. In addition, bank size has a positive impact on return on assets. It means that increase in bank size leads to increase in return on assets. Similarly, capital adequacy ratio has a positive impact on return on assets. It means that increase in capital adequacy ratio leads to increase in return on assets.